Penerapan Sistem Pakar dengan Metode Naive Bayes pada Kerusakan Motor Injeksi - Sinaga, Marito Romaida; Sianipar, Lilin; Laia, Naomita; Bawamenewi, Nelis Sastraman; Surbakti, Asprina Br; Danur, Surizar Rahmi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
An injection engine is a motorized vehicle that uses a fuel injection system directly into the combustion chamber through an injector that is electronically controlled by the ECU. However, mechanics often encounter obstacles and difficulties in checking for damage to the injection engine, so that checks are still carried out manually on the injection engine. To overcome this problem, one solution is to utilize an analysis method that can help and facilitate mechanics in determining damage to the injection engine. This method was chosen with the aim of being able to identify the type of damage and provide solutions related to existing problems. The purpose of this study is to analyze and identify the types of damage to the injection engine using the Naïve Bayes method, as well as to determine the probability level of each damage so that it can provide more accurate information for the repair process. The results of the calculation test using the Naïve Bayes method show that problematic injection sensor damage is the damage with the highest value of 72.8%.